Dissemination and Systemic Colonization of Uropathogenic Escherichia coli in a Murine Model of Bacteremia - Sara N. Smith (American Society for Microbiology, 2010)
ABSTRACT Infection with uropathogenic Escherichia coli (UPEC), the causative agent of most uncomplicated urinary tract infections, proceeds in an ascending manner and, if left untreated, may result in bacteremia and urosepsis. To examine the fate of UPEC after its entry into the bloodstream, we developed a murine model of sublethal bacteremia. CBA/J mice were inoculated intravenously with 1 × 106 CFU of pyelonephritis strain E. coli CFT073 carrying a bioluminescent reporter. Biophotonic imaging, used to monitor the infection over 48 h, demonstrated that the bacteria disseminated systemically and appeared to localize at discrete sites. UPEC was recovered from the spleen, liver, kidneys, lungs, heart, brain, and intestines as early as 20 min postinoculation, peaking at 24 h postinoculation. A nonpathogenic E. coli K-12 strain, however, disseminated at significantly lower levels (P < 0.01) and was cleared from the liver and cecum by 24 h postinoculation. Isogenic mutants lacking type 1 fimbriae, P fimbriae, capsule, TonB, the heme receptors Hma and ChuA, or particularly the sialic acid catabolism enzyme NanA were significantly outcompeted by wild-type CFT073 during bacteremia (P < 0.05), while flagellin and hemolysin mutants were not. IMPORTANCE E. coli is the primary cause of urinary tract infections. In severe cases of kidney infection, bacteria can enter the bloodstream and cause systemic disease. While the ability of E. coli to cause urinary tract infection has been extensively studied, the fate of these bacteria once they enter the bloodstream is largely unknown. Here we used an imaging technique to develop a mouse model of E. coli bloodstream infection and identify bacterial genes that are important for the bacteria to spread to and infect various organs. Understanding how urinary tract pathogens like E. coli cause disease after they enter the bloodstream may aid in the development of protective and therapeutic treatments.